Tailor-Made Immunochromatographic Test for the Detection of Multiple 17α-Methylated Anabolics in Dietary Supplements - Holubová, Barbora; Kubešová, Pavla; Huml, Lukáš; Vlach, Miroslav; Lapčík, Oldřich; Jurášek, Michal; Fukal, Ladislav (Foods (Basel, Switzerland), 2021)
In recent years, the undeclared presence of various anabolic androgenic steroids (AAS) in commercial supplements has been confirmed. This fact can be a potential threat to all athletes using these supplements, and therefore, there is of increased interest in the implementation of rapid methods for the detection of AAS. The presented study describes the development of an immunostrip test for the detection of multiple 17α-methylated AAS based on direct and indirect competitive principle using gold nanoparticles as a label. As a capture reagent on test lines conjugated stanazolol to rabbit serum albumin (RSA/ST-3) was used, the intensity of color formed in the test line of the AAS-positive sample was visually distinguishable from that of negative sample within 10 min. The optimized closed direct and indirect format of the test provided a similar visual detection limit (0.7 and 0.9 ng/mL, respectively). The most commonly orally abused AAS (17α-methyltestosterone, methandienone, methyldihydrotestosterone, oxandrolone and oxymetholone) showed a strong cross-reaction. Developed immunostrips were successfully applied to analysis of artificially contaminated dietary supplements with 17α-methylated AASs. The developed immunostrips offer potential as a useful user-friendly method for capturing suspicious dietary supplement samples with different contents of AAS at levels far below the usually used concentrations of AAS.
Keywords: stanazolol; dietary supplements; anabolic steroids (AAS); 17α-methylated AAS; immunochromatography